A full numerical model for the installation analysis of suction caissons in sand. (15th August 2021) - Harireche, Ouahid; Naqash, Muhammad Tayyab; Farooq, Qazi Umar
Abstract: Safe installation of suction caissons requires a reliable preliminary study where soil resistance and other soil conditions are predicted with good accuracy. Past studies did not address the full problem when modelling the installation procedure of suction caissons in sand. Suction was prescribed at the mudline and soil resistance was predicted based on soil properties and the resulting seepage profile around the caisson wall. Suction magnitude was assumed to overcome soil resistance, limiting its magnitude to avoid critical conditions such as piping. Most of these studies did not address other important parameters such as pumping rate and water depth. This paper addresses the following points: Feasibility of the installation depends on the water depth and hence, this must be specified as part of the installation design. Suction magnitude in excess to the initial hydrostatic pressure corresponds to a certain pumping rate, which is the parameter to control for a safe installation. A full numerical model is proposed in this paper to consider a prescribed pumping rate at the center of the caisson lid and the resulting flow inside the caisson cavity. The model was implemented in COMSOL Multiphysics and used to perform simulations of suction assisted installation in sand. Prescribed pumping rates have been investigated in conjunction with mobilized soil resistance, critical piping, water depth and available driving pressure. Highlights: Installation of suction Caisson foundations in sand is revisited to consider more adequate parameters. A full numerical model is developed to perform simulations of the installation under prescribed pumping rates. Feasibility and safety of the installation process are assessed based on the prescribed pumping rate.